BAGAIMANA BUKTI AUDIT DAPAT MENGUNGKAP FRAUD? - Dina Fitri Septarini (EKONOMI & SOSIAL, 2014)
The purpose of this paper is to describe the use of audit evidence in fraud detection. This is because the detection of fraud is not an easy task to be undertaken by auditors, and even most of the auditors were unable to detect fraud as well. To be used to detect fraud, audit evidence must be sufficient, competent, and relevant. Furthermore, to assess their validity, the evidence collected should be tested first. An auditor also needs to have professional skepticism when gathering and evaluating audit evidence. Without applying professional skepticism, auditors will only find misstatements caused by error only and hard to find fraud.For the detection of fraud within the organization, fraud categorized into three groups, namely fraudulent financial reporting, misappropriation of assets, and corruption. Each type of fraud has its own characteristics, so as to be able to detect the fraud it is necessary to understand well the types of fraud that may arise within the company.